A bioclimatic analysis tool for investigation of the potential of passive cooling and heating strategies in a composite Indian climate. (October 2017) - Khambadkone, Naveen Kishore; Jain, Rekha
Abstract: India is divided into five major bioclimatic zones, out of which the composite zone covers more than 30% of the geographic area. The current bioclimatic classification and thermal comfort criteria delineated in the National Building Code do not adequately address the climatic diversity of the country. Moreover, existing climate analysis software tools fail to predict comfort potential for Indian conditions accurately. Henceforth, the main aim of this paper is to develop a bioclimatic analysis tool to investigate the comfort potential of different passive heating and cooling strategies for locations with a composite climate in India. Three sites, namely New Delhi, Bhopal, and Hyderabad, are taken up as case study cities. A modified comfort zone is proposed on the bioclimatic chart based on Tropical Summer Index (TSI). The comfort zone of the chart was extended to define the passive design zones based on the calculations of the effects of passive heating and cooling strategies. The effectiveness of three passive strategies, namely natural ventilation, direct evaporative cooling and passive solar heating is demonstrated through the tool. Results derived from the tool show that natural comfort potential can vary between 25 and 46% of the total time of a year depending on the location. Further predictions by the tool show natural ventilation to be an effective strategy for all three areas. The tool can also be used to provide passive design recommendations for different cities. The findings of the tool can have significant implications for the development of energy-efficient buildings by Architects. Highlights: We propose a new bioclimatic analysis tool for composite climate zone of India. Natural comfort potential varies between 25 and 46% of time of year based on location. Passive comfort potential increases from 74 to 91% geographically from north to south. Natural ventilation is the most effective passive strategy for composite climate.